Gene-Environment Interactions in Major Mental Disorders in the Czech Republic - Latalova, Klara; Sery, Omar; Hosakova, Kristyna; Hosak, Ladislav (Neuropsychiatric disease and treatment, 2020)
BACKGROUND: Mental disorders affect about one﻿-third of the human population, are typically chronic and significantly decrease the quality of life. Presently, the treatment of mental illnesses is far from adequate with a substantial proportion of the patients being pharmacoresistant and suffering from relapses. One of the reasons for this complicated situation is that we do not precisely know about the causes of mental disorders, so their treatment cannot be causal. The etiology of a mental disorder is typically based on a combination of molecular (genetic) and environmental factors. AIM: The aim of the project is to discover the gene-environment interactions (GxE) in a wide spectrum of mental disorders. METHODS: The design of our study is innovative in the sense that we intend to study large groups of associated mental disorders as a whole instead of in isolation. This would enable us to map out the possible environmental causal factors in detail in relation to their character, magnitude and timing. The project also allows a study of genetics (including epigenetics and microbiomes) as well as the environment simultaneously. We plan on involving three study groups: the first group are patients suffering from schizophrenia or a mood disorder such as major depression, recurrent depressive disorder and bipolar affective disorder; the second group of patients have anxiety disorders; and the third group are healthy volunteers from the general population who are genetically unrelated. All of the study subjects will undergo the following assessments: a psychiatric examination, the identification of stressful life events with the aid of a questionnaire, the examination of their reaction to stress, genetic and epigenetic (microRNA) assessments and the analysis of oral and gut microbiome. CONCLUSION: We expect that some of the genetic as well as environmental factors in the studied mental disorders are shared, while some others are specific. We also expect that the GxE (gene-environment interaction) in schizophrenic and affective disorders will be different from the GxE in anxiety disorders and that the GxE in the studied mental disorders will differ generally from the GxE in healthy volunteers. Our results can help in the prevention and individualized treatment of a range of mental disorders.
Keywords: gene; anxiety disorders; schizophrenia; environment; GxE interactions; mood disorders